Rancang Bangun Sistem Informasi Pengukuran Tingkat Kepuasan Pelanggan Berdasarkan Kualitas Pelayanan E-Government Menggunakan Metode Regresi - Danar Yudhistira, Arnoldus Yansen Friska; Wibowo, Januar; Sulistiowati, Sulistiowati (Jurnal JSIKA, 2012)
In order to measure customer satisfaction levels on giving an e-government services, the government of surabaya needs to design information systems using a modeling of service quality (servqual) wich is based on website. This customer satisfaction information system uses multiple regression test, the statistics test to find the influence of customer satisfaction with quality of e-procurement service of the Surabaya’s Government. The purpose of this study is to provide important information for the head of Bina Program Division and for all of Surabaya civilian as the recipients of services. The data was collected by questionnaire in the form of qualitative data collection. Then it converted into quantitative data using likert scaling techniques. To get the value of the regression coefficient it must be invers using Elementary Row Transformation. To search an independent variables that influence to the dependent variable used by T test. To find the influence of all independent variables on the dependent variable used F Test. R2 is a number in the program showed significant 0.54435348292734 or 54% of customers indicate satisfaction. From the results of F test and T test program finds all the independent variables affected to the dependent variable. Wich is the variable X5 or Tangible dimension greater influence than the others. Keyword: Information System of Customer Satisfaction Measurement, Multiple Regression Analysis, E-Procurement System of Surabaya‘s Government